An untethered C3v-symmetric triarylphosphine oxide locked by intermolecular hydrogen bonding. Issue 26 (13th March 2019) - Carroll, Timothy G.; Hunt, Camden; Garwick, Rachel; Wu, Guang; Dobrovetsky, Roman; Ménard, Gabriel
Abstract : A C 3v -symmetric triarylphosphine oxide locked into conformation by H-bonding and displaying an extended MOF-like solid-state structure is reported. Abstract : A para -substituted triphenylphosphine oxide with terminal vanadocene centers has been prepared and is, to our knowledge, the first example of an untethered C 3v -symmetric triarylphosphine oxide in the solid state. Crystallographic and DFT studies suggest this locked conformation is due to intermolecular H-bonding interactions. Electrochemical measurements suggest these interactions may persist in solution. A monometallic variant, adopting the standard C 3 propeller geometry, has also been synthesized for comparison.